The Relation of Perceived Meaning of Life, Meaning of Illness and Anxious-Depressive Symptoms among Cancer Patients - Elekes, Szende (European Journal of Mental Health, 2017)
Our research is based on the literature that shows meaningfulness is a correlate of mental health both in the general population and in the case of patients with a serious illness such as cancer. We had two major goals: 1) to identify the meaning-categories patients find in their illness; 2) to test the relationships between perceived meaning of life, meaning of illness and negative indicators of well-being, like automatic thoughts, anxiety, depression in the case of a population of cancer patients from Romania. This study was completed in March-June of 2012. A number of 102 cancer patients, interned in the ‘Ion Chiricuta- Oncology Institute in Romania, completed a battery of scales that measured perceived meaning of life (Meaning in Life Questionnaire, Meaning in Life after Cancer), the intensity of automatic thoughts (Automatic Thoughts Questionnaire), anxiety, depression (Hospital Anxiety and Depression Scale), and answered the question whether they found any meaning in their lives. We could identify the following categories of meaning patients found in their illness: character change, greater appreciation of life, change of priorities, spiritual growth, greater appreciation of close relationships, clarification of goals, development of self-knowledge. In accordance with the literature, our results show that perceived meaning of life (measured by MLaC), correlates negatively with automatic thoughts (r = -0.606), anxiety (r = -0.576), and depression (r = -0.542), and these relations are significant (p = 0.000). Patients who found their illness meaningful, found more meaning in their lives as well (t = 3.041, p = 0.003), and they showed lower levels of anxiety and depression, but these correlations are not significant (p = 0.567 and 0.116).